(untitled) (AYUSHDHARA, 2021)
Woman’s health is point of concern for her family, society and culture because any physical or mental disturbance can disturb her normal menstrual cycle. Asrigdara is the common gynecological problem from menarche to menopause affecting her day to day activities. It is one of the Raktadoshaja Vikara manifesting as excessive menstrual bleeding or intermenstrual bleeding different from the features of normal menstrual blood. On the basis of its symptomatology, it can be compared with abnormal uterine bleeding. It is a debilitating disorder affecting the physical and psychological health of women which finally results in hysterectomy if not treated properly. Nidana is the main causative factor in initiating the Samprapti of the disease. In Samprapti of Asrigdara, various etiological factors such as Lavana, Amla and Katu Rasa, Guru, Vidahi and Snigdha Annapana, Dadhi, Sukta, Mastu etc leads to vitiation of Vata Pitta Dosha and Rakta Dhatu resulting in Asrigdara Vyadhi. In the present study an effort was made to analyse Nidanas in the pathogenesis of the disease on the basis of involvement of Doshas and Dhatus. In Ayurveda classics, Nidana Parivarjan is mentioned as the first line of treatment for any disease. Understanding the Nidanas of Asrigdara plays a major role in the diagnosis, prevention and treatment of the disease.